2022
DOI: 10.1155/2022/9371818
|View full text |Cite
|
Sign up to set email alerts
|

Complete AV Block in Vaccinated COVID-19 Patient

Abstract: Background. Coronavirus 2019 (COVID-19) was initially identified approximately in December 2019 at Wuhan, China, as patients presented with vague prodromal and respiratory symptoms. With the developing investigation of its clinical manifestation, cardiac symptoms have been widely reported including acute coronary syndromes, myocarditis, arrhythmias, heart failure, and cardiac arrest. Case Summary. An 84 year-old male with history of coronary artery disease, hypertension, and hyperlipidemia presented to an outs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…The intraoperative management of heart disease patients with a COVID-19 infection history (ongoing infectious phase or postinfectious recovery phase) has not been clearly determined yet, but COVID-19 infection may possibly contribute to the deterioration of the cardiac conduction system, such as sinus node disease or high degree AV block [ 23 , 24 ]. Cardiac electrophysiologic therapy has continuously played a reliable role to help COVID-19 patients recover from fatal arrhythmia despite the concerns of difficult lead positioning, health care providers safety, and the reduction of de novo implantation [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…The intraoperative management of heart disease patients with a COVID-19 infection history (ongoing infectious phase or postinfectious recovery phase) has not been clearly determined yet, but COVID-19 infection may possibly contribute to the deterioration of the cardiac conduction system, such as sinus node disease or high degree AV block [ 23 , 24 ]. Cardiac electrophysiologic therapy has continuously played a reliable role to help COVID-19 patients recover from fatal arrhythmia despite the concerns of difficult lead positioning, health care providers safety, and the reduction of de novo implantation [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…One hundred fourteen studies were further excluded after screening for title and abstract. Of the remaining 25 articles, four studies focused on complications other than vaccination, [20][21][22][23] one study focused on non-TTS cardiac complications after vaccination, 24 and two studies were not case reports or case series. 25,26 Those studies were excluded as a result.…”
Section: Study Selectionmentioning
confidence: 99%
“…Cardiac injury following COVID-19 infection is now well described in the literature, although the mechanisms behind this remain uncertain (7). Clinical studies have reported post-covid complications such as thromboembolism, ischaemia, arrhythmias, conduction defections and myocarditis (18)(19)(20) and post-mortem studies have found increased neutrophil extracellular trap (NET) formation and mononuclear cell infiltration (9). Given that cardiac involvement is an important and long-term consequence of COVID-19, and potential also within the spectrum of syndromes observed in "long-COVID", we examined post-mortem heart tissue for DSG2 protein.…”
Section: (Which Was Not Certified By Peer Review)mentioning
confidence: 99%